Enhancing Listening Skills in Arabic Language Learning: An Innovative Approach Using Animated Films - Suryanata, Helmi; Anwar, Najih (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the application of animated Arabic films as a modern technological innovation to improve the listening skills of seventh-grade students at SMPIT AL-Khwarizmi Paser. Employing a class action research method over two cycles, the research employed qualitative and quantitative data, including observations, interviews, documentation, and test scores. The results indicate significant improvements in students' listening skills, with a noteworthy 11.76% increase in classical completeness rates from the first to the second cycle. This innovative approach offers valuable implications for enhancing listening skills in Arabic language education, highlighting the potential of animated films as effective learning media. Highlights: Effective Pedagogical Tool: The study underscores animated Arabic films as a potent pedagogical tool for enhancing listening skills in language education. Quantifiable Improvement: It demonstrates a significant 11.76% increase in students' classical completeness rates, indicating tangible progress. Innovative Language Learning: This research highlights the innovative use of technology to facilitate language learning, with implications for broader educational contexts. Keywords: Arabic language learning, listening skills, animated films, innovation, student performance.